Bacterial Contamination of Blood and Blood Products at Mbarara Regional Blood Bank in Rural South Western Uganda - Aloysius, G. B. Matte; Joel, Bazira; Apecu, Richard; II, Boum Yap; Byarugaba, Frederick (Advances in Infectious Diseases, 2013)
Background: Screening blood donors has practically eliminated viral and bacterial pathogens in blood used for trans- fusion. However, transfusion-associated bacterial sepsis remains an important health-care concern and the commonest cause of transfusion-related fatality in resource limited settings. Data on bacterial contamination of blood are scarce while the demand of blood transfusion is continuously growing. Therefore we conducted a study to determine the prevalence and type of bacterial contamination in donor blood and blood products, at the Mbarara Regional Blood Bank. Methodology: A total of 510 units of screened blood and blood products consisting of refrigerated whole blood and packed cells were randomly sampled following aseptic procedures from Mbarara Regional Blood Bank. Two samples from each unit were collected in universal containers containing Brain Heart Infusion Broth and incubated at 37°C for up to 7 days. Subcultures were carried out on Blood agar, Chocolate agar and MacConkey agar. Isolates were identified by standard microbiologic techniques and drug susceptibility testing was performed by Kirby Bauer disc diffusion method. Results: Of the 510 samples collected between June and October 2012, 18 (3.5%) samples showed growth. The contaminants were Staphylococcus aureus 17/18 (94.4%) and Streptococcus viridans 1/18 (5.6%). Isolates were sensitive to erythomycin, ampicillin, chloramphenicol and ciprofloxacin and resistant to penicillin and cloxacillin. Conclusion: Blood and blood products from Mbarara Regional Blood have unacceptable levels of bacterial contamination that can affect patient safety especially in an area with high malaria endemicity. Therefore it is critical to improve hy- giene precautions in order to minimize bacterial contamination and ensure patient safety.
Keywords: Bacterial Contamination; Blood/Blood Products; Staphylococci